2007
DOI: 10.1177/1077559507299292
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Parental Alcohol or Drug Removals on Foster Care Placement Experiences: A Matched Comparison Group Study

Abstract: Research has established the coincidence of parental alcohol and other drug (AOD) use and child maltreatment, but few studies have examined the placement experiences and outcomes of children removed due to parental AOD use. The present study examines the demographic characteristics and placement experiences of a sample of children removed from their homes as a result of parental AOD use (n=1,333), first in comparison to the remaining sample of children in foster care (n=4554), then to a matched comparison grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…Parental substance abuse has been identified as a primary contributor to child maltreatment (Dong et al, 2004) and has been indicated or suspected in more than two-thirds of all substantiated cases (Jones, 2005). Children of parents who abuse substances are much more likely to be placed in foster care (U. S. Department of Health and Human Services, 1999;Young, Boles, & Otero, 2007) and are in out-of-home placements longer than youth removed for other reasons (Vanderploeg et al, 2007). Moreover, substance abuse often co-occurs with IPV, and has been documented in both victims (El-Bassel, Gilbert, Wu, Go, & Hill, 2005) and perpetrators (Fals-Stewart, Golden, & Schumacher, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…Parental substance abuse has been identified as a primary contributor to child maltreatment (Dong et al, 2004) and has been indicated or suspected in more than two-thirds of all substantiated cases (Jones, 2005). Children of parents who abuse substances are much more likely to be placed in foster care (U. S. Department of Health and Human Services, 1999;Young, Boles, & Otero, 2007) and are in out-of-home placements longer than youth removed for other reasons (Vanderploeg et al, 2007). Moreover, substance abuse often co-occurs with IPV, and has been documented in both victims (El-Bassel, Gilbert, Wu, Go, & Hill, 2005) and perpetrators (Fals-Stewart, Golden, & Schumacher, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…Research on families in child welfare, parents in treatment, and families of substance-exposed infants suggests that a majority of families involved or at risk for involvement in the child welfare system in the United States are impacted by parental substance abuse problems (Boles, Young, Moore, & DiPirro-Beard, 2007;Carter & Myers, 2007;Connell-Carrick, 2007;Smith, Johnson, Pears, Fisher, & DeGarmo, 2007;Vanderploeg, Caron, Saunders, Katz, & Tebes, 2007;Young, Boles, & Otero, 2007). Concern over the correlation between substance abuse and child welfare, as well as growing recognition of the importance of consistency in caretaking in child development, has generated a number of policy changes on both national and state levels.…”
Section: Introductionmentioning
confidence: 99%
“…Some research also suggests that the mother’s mental health issues may exacerbate their experience (Mezulis et al, 2004). Among child welfare cases, substance abuse is associated with higher rates of child re-victimization (Brook & McDonald, 2009; Ondersma, 2007), greater likelihood of out of-home placement (DHHS, 1997), longer stays in care (Connell et al, 2007; Vanderploeg et al, 2007), and higher rates of termination of parental rights and child adoption (Connell et al, 2007). In addition, substance use disorders (SUD) are related to fathers’ decreased involvement and to their own children developing SUDs (Kirisci et al, 2001).…”
Section: Discussionmentioning
confidence: 99%